2004
DOI: 10.1002/chp.1340240105
|View full text |Cite
|
Sign up to set email alerts
|

eLearning: A review of Internet-based continuing medical education

Abstract: The results demonstrate that Internet-based CME programs are just as effective in imparting knowledge as traditional formats of CME. Little is known as to whether these positive changes in knowledge are translated into changes in practice. Subjective reports of change in physician behavior should be confirmed through chart review or other objective measures. Additional studies need to be performed to assess how long these new learned behaviors could be sustained. eLearning will continue to evolve as new innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
218
0
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(228 citation statements)
references
References 23 publications
3
218
0
7
Order By: Relevance
“…An active attitude combined with the ability to choose the moment of participation may improve learning efficiency. Wutoh et al reviewed the effect of interventions with internet-based continuing medical education on the performance of physicians and healthcare outcomes 13 . The results demonstrated that internet-based continuing medical education programs are just as effective in imparting knowledge as traditional formats of continuing medical education.…”
Section: Discussionmentioning
confidence: 99%
“…An active attitude combined with the ability to choose the moment of participation may improve learning efficiency. Wutoh et al reviewed the effect of interventions with internet-based continuing medical education on the performance of physicians and healthcare outcomes 13 . The results demonstrated that internet-based continuing medical education programs are just as effective in imparting knowledge as traditional formats of continuing medical education.…”
Section: Discussionmentioning
confidence: 99%
“…The results reported here are similar to those from previous studies that have compared online and classroom education in other disciplines. 2,3,17 Although satisfaction with the 2 modes of delivery was high and similar, participants made more negative anecdotal comments about the EOM than about the F2FL sessions.…”
Section: Discussionmentioning
confidence: 99%
“…They are also allocated one week per year of paid continuing medical education of their selection and are encouraged to attend any medical conferences held locally. This may be why we 8,9 suggests an increased use of electronic educational options and that Internet-based continuing medical education programs are just as effective in imparting knowledge as are traditional formats. The significantly greater use of the Internet than was intended by the physicians in our study likely reflects the growing use of this technology as a gateway to learning.…”
Section: Discussionmentioning
confidence: 99%